How Artificial Intelligence (AI) Can Support Developing Curriculums in Education and for Research - Safaeimanesh, Farzad; Güden, Nafiya; Safaeimanesh, Shahrzad (IGI Global, 2024)
Education is the power behind developing communities and nations, it is what shapes the economy as well as encourages peace in societies and ecological environments. Therefore, we cannot avoid the importance of education in developing humanity for the future. It is evident that Artificial Intelligence (AI) supports this power, enhancing it on the one hand, and making sharing knowledge more efficient in our busy lifestyles in this technological era, on the other. Throughout this chapter, we provide the audiences with the definition of AI, its types, and its importance in education and research along with the concerns and challenges. In addition, this chapter presents the agenda for researchers and educators on how to use generative AI during their research processes and education systems to be sound and of course ethical by suggesting how and where AI can be helpful. © 2025 by IGI Global. All rights reserved.
Keywords: Curricula; Engineering education; Engineering research; Developing communities; Developing nations; Ecological environments; Education and researches; Intelligence support; Power; Process system; Research process; Sharing knowledge; Society environment; Teaching